Tissue damage in the canine normal esophagus by photoactivation with talaporfin sodium (laserphyrin): a preclinical study. - Takahiro Horimatsu; Manabu Muto; Yusuke Yoda; Tomonori Yano; Yasumasa Ezoe; Shinichi Miyamoto; Tsutomu Chiba (PLoS ONE, 2012)
BACKGROUND: Treatment failure at the primary site after chemoradiotherapy is a major problem in achieving a complete response. Photodynamic therapy (PDT) with porfimer sodium (Photofrin®) has some problems such as the requirement for shielding from light for several weeks and a high incidence of skin phototoxicity. PDT with talaporfin sodium (Laserphyrin) is less toxic and is expected to have a better effect compared with Photofrin PDT. However, Laserphyrin PDT is not approved for use in the esophagus. In this preclinical study, we investigated tissue damage of the canine normal esophagus caused by photoactivation with Laserphyrin. METHODOLOGY/PRINCIPAL FINDINGS: Diode laser irradiation was performed at 60 min after administration. An area 5 cm oral to the esophagogastric junction was irradiated at 25 J/cm(2), 50 J/cm(2), and 100 J/cm(2) using a three-step escalation. The irradiated areas were evaluated endoscopically on postirradiation days 1 and 7, and were subjected to histological examination after autopsy. The areas injured by photoactivation were 52 mm(2), 498 mm(2), and 831 mm(2) after irradiation at 25 J/cm(2), 50 J/cm(2), and 100 J/cm(2), respectively. Tissue injury was observed in the muscle layer or even deeper at any irradiation level and became more severe as the irradiation dose increased. At 100 J/cm(2) both inflammatory changes and necrosis were seen histologically in extra-adventitial tissue. CONCLUSIONS/SIGNIFICANCE: To minimize injury of the normal esophagus by photoactivation with Laserphyrin, diode laser irradiation at 25 J/cm(2) appears to be safe. For human application, it would be desirable to investigate the optimal laser dose starting from this level.